Intercultural friendship formation of Japanese university students: social anxiety may shape their priorities and agency - Guinea-Takagi, Naomi; Ishikawa, Mitsuhiko; Sudo, Mioko (Frontiers in Communication, 2026)
We examined which affinity-inducing factors Japanese university students (N = 46) consider important in intercultural friendship formation, and whether social anxiety and autistic tendencies shape their perceived importance of these factors and their agency in past intercultural friendships. Participants indicated the factors they considered most important in forming intercultural friendships, described their past experiences of intercultural friendship formation, and completed measures of social anxiety and autistic tendencies. Results suggest that the culturally distinct partner’s interpersonal qualities (i.e., sociability and generosity), proximity, and similar interests were the most important factors. Lower social anxiety significantly predicted the selection of the partner’s generosity as important, while higher social anxiety significantly predicted a greater likelihood of having taken non-agentive than agentive roles in past intercultural friendships. These findings may reflect differing levels of sensitivity toward uncertainty in intercultural interactions. Autistic tendencies did not predict factor selection or role types.